Loneliness and social isolation: exploring the experiences of older women during the pandemic in terms of social connection, feeling of loneliness, and the impact on mental health and wellbeing - Bhat, Nasrullah; Paul, Fayaz Ahmad; Gul, Aamir; Ganie, Zahoor Ahmad (Frontiers in Global Women's Health, 2024)
Objectives: To investigate the unique challenges faced by older women during the COVID-19 pandemic regarding social connection, feelings of loneliness, and their subsequent impact on mental health and well-being Method: A qualitative research methodology is used to examine how older women experienced loneliness, social relationships, and mental health consequences during the COVID-19 pandemicThe results are discussed in terms of two main themes each with their sub-themes; 1. Social Connection amidst Physical Distancing Measures, 2. Impact on Mental Health and Well-being.The study highlights the significant impact of loneliness and social isolation on the mental health of older women during the COVID-19 pandemic, emphasizing the need for targeted interventions and support systems.